2007
DOI: 10.1002/ijc.22811
|View full text |Cite
|
Sign up to set email alerts
|

Folate receptor overexpression is associated with poor outcome in breast cancer

Abstract: The high affinity folate receptor is a membrane-associated glycoprotein that is preferentially expressed in cancers of epithelial origin and rarely expressed in normal cells. We examined its expression pattern in breast cancer, utilizing a tissue microarray containing samples from 63 invasive breast cancers from women with divergent clinical outcomes. Thirty-three women comprised the poor outcome group with a median time to recurrence of 1.9 years. Thirty women, the good outcome group, were free of recurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
139
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(147 citation statements)
references
References 27 publications
6
139
1
1
Order By: Relevance
“…only 20 high-stage, high-grade serous tumors lacked FRĪ± expression in this study), very large sample sizes will be required to accrue sufficient numbers of patients with FRĪ±-negative tumors for statistically meaningful comparisons. This makes analysis of the impact of FRĪ± expression in ovarian cancer rather more difficult than in breast and uterine cancers; in these diseases, with strong FRĪ± expression in a smaller proportion of patients, FRĪ± expression is a negative prognostic factor [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…only 20 high-stage, high-grade serous tumors lacked FRĪ± expression in this study), very large sample sizes will be required to accrue sufficient numbers of patients with FRĪ±-negative tumors for statistically meaningful comparisons. This makes analysis of the impact of FRĪ± expression in ovarian cancer rather more difficult than in breast and uterine cancers; in these diseases, with strong FRĪ± expression in a smaller proportion of patients, FRĪ± expression is a negative prognostic factor [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Such an observation is in line with our previous findings in primary colorectal cancers, as well as that observed in ovarian, breast and endometrial carcinoma. [9][10][11] In all of these tumor types including both primary and metastatic colorectal cancer, overexpression of FRa detected by immunohistochemistry had either a strong trend towards, or significantly correlated with a worse survival. Interestingly, however, a study that evaluated 119 non-small cell lung cancers found high FRa expression to be correlated with a better survival.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Its expression in certain epithelial tumors such as ovarian, breast, endometrial and non-small cell lung carcinoma has been associated with tumor behavior. [9][10][11][12] Importantly, FRa expression is tumor specific, as it is significantly higher in tumor cells than in normal cells. 13 FRa also has a high affinity for folic acid; and the high affinity is maintained when folic acid is conjugated with other molecules.…”
mentioning
confidence: 99%
“…The FR is rarely expressed in normal tissues, 1,2 is highly expressed in breast cancer, endometrial cancer, nonmucinous ovarian adenocarcinoma, lung cancer, kidney cancer, and pancreatic cancer, and is known as a tumor-associated antigen. [3][4][5][6] Folic acid (FA) is a water-soluble B vitamin, and is used in cells to synthesize thymine, which is critical for DNA synthesis, methylation, and repair. Folic acid is small (441 Da), stable over a broad range of temperatures and pH values, inexpensive, and nonimmunogenic.…”
Section: Introductionmentioning
confidence: 99%